The Synthesis of Reality as an Architecture Principle: Architecture and Society. (EAAE Annual Conference Proceedings, 2025)
This paper presents a pedagogical model based on over a decade of collaborative teaching experiences involving universities and non-academic entities, including governmental and non-governmental organizations. The initiative seeks to foster a sustained dialogue between academia and society through a dynamic integration of critical and experimental thinking, aimed at addressing the complex and evolving needs of contemporary contexts.Grounded in the premise that the future must be informed by both a reflective engagement with the past and a rigorous understanding of the present, this approach emphasizes shared methodologies and collaborative diagnostics. These are seen as essential for developing complex, yet contextually grounded, educational models that promote social relevance and transformative practice.At the core of these initiatives is Architects Without Borders, whose partnerships with academic institutions have helped shape educational frameworks aligned with the principles of cooperative architecture. This includes real-world exercises designed in close collaboration with communities, thereby simulating practice-based learning environments. The model emphasizes proximity architecture – an approach that prioritizes co-creation with end users as a critical strategy for producing socially responsible design.This experience highlights the potential of transdisciplinary collaboration in architectural education to produce more engaged, responsive, and contextually attuned professional practice.In this paper are explored programs such as “ Territorios Colaborativos” (cooperative territories) promoted by the university ISCTE in Lisbon and “Arquitectura e Sociedade” (Architecture and Society) promoted by FAUP in Porto.Nunes, Ligia, A. Paio, e David Leite Viana. “Territórios colaborativos: nuevos desafíos en la educación universitaria.”. Arcadia5: Architecture and Cooperation for Development Congress, País Basco, Espanha, 2018. Silva, Ligia da. “Escoles d’intervenció i treballs de cooperació sobre el Patrimoni.” Jornades Internacionals sobre La Intervenció en el Patrimoni Arquitectònic, Barcelona, 2015.Smith, John, and Maria Gonzalez, eds. Emerging Perspectives on Teaching Architecture and Urbanism. New York: Routledge, 2023.